The discovery of three new hare lagoviruses reveals unexplored viral diversity in this genus. Issue 1 (9th April 2019) - Mahar, Jackie E; Hall, Robyn N; Shi, Mang; Mourant, Roslyn; Huang, Nina; Strive, Tanja; Holmes, Edward C
Abstract: Our knowledge of mammalian viruses has been strongly skewed toward those that cause disease in humans and animals. However, recent metagenomic studies indicate that most apparently healthy organisms carry viruses, and that these seemingly benign viruses may comprise the bulk of virus diversity. The bias toward studying viruses associated with overt disease is apparent in the lagoviruses (family Caliciviridae) that infect rabbits and hares: although most attention has been directed toward the highly pathogenic members of this genus—rabbit haemorrhagic disease virus and European brown hare syndrome virus—a number of benign lagoviruses have also been identified. To determine whether wild European brown hares in Australia might also carry undetected benign viruses, we used a meta-transcriptomics approach to explore the gut and liver RNA viromes of these invasive animals. This led to the discovery of three new lagoviruses. While one was only detected in a single hare, the other two viruses were detected in 20 per cent of all animals tested. All three viruses were most closely related to other hare lagoviruses, but were phylogenetically distinct from both known viruses and from each other, indicating that lagoviruses have circulated for longer than previously assumed. Their evolution was also characterised by complex recombination events. Mapping mutations onto the lagovirus phylogeny revealed no amino acid changes that were consistently associated with virulence phenotype. Overall, our study points to extensive unsampled diversity in this genus, such that additional metagenomic studies are needed to fill gaps in the lagovirus phylogeny and better understand the evolutionary history of this important group of mammalian viruses.